Description of the sexuales of Myzodium modestum (Hottes) (Hemiptera: Aphididae) discovered in the Swiss Alps - Hidalgo, Nicolás Pérez; Vandegehuchte, Martijn L.; Schütz, Martin; Risch, Anita C. (Zootaxa, 2016)
The sexuales (apterous oviparous female and alate male) of Myzodium modestum (Hottes) are described for the first time from specimens captured in the Swiss Alps. This is also the first record of this species in Switzerland. This is the first evidence that an aphid may be able to complete its life cycle on mosses.